Factores asociados a conocimientos, actitudes y prácticas preventivas hacia el COVID-19 en profesionales dela salud en Lima, Perú - Lozada de Bonilla, Oriana Rivera (Universidad Peruana Unión, 2021)
Background: Nowadays, we are facing a disease caused by SARS-CoV-2, known globally as COVID-19, which is considered a threat to global health due to its high contagiousness and rapid spread. Methods: Analytical cross-sectional study in 302 health professionals. An online questionnaire consisting of questions about knowledge, attitudes and practices (KAP) towards COVID-19 was applied. Socio-demographic, occupational and comorbidities factors were explored. Simple and multiple logistic regression models were used to identify factors associated with KAP. Results: Of the total, 25.2%, 31.5% and 37.4% had high levels of knowledge, preventive practices and risk perception attitudes respectively. Being married (aOR=6.75), having a master's degree (aOR= 0.41), having a working day with less than ten hours (ORa=0.49) and obesity (aOR=0.38) were associated with a low level of knowledge of COVID-19. The variables associated with preventive practices were being over the age of 50 (aOR=0.52), working in the hospitalization area (aOR=1.86) and having comorbidities such as arterial hypertension (aOR=0.28) and obesity (aOR=0.35). In relation to negative attitudes towards COVID 19, it was found that physical contact with patients with a confirmed diagnosis (aOR=1.84) and having asthma (aOR=2.13) were associated with these attitudes. Conclusion: Being married, having a master's degree, working less than ten hours were associated with having a low level of knowledge of COVID-19. Being older than 50, working in the hospitalization area were associated with preventive practices. Physical contact with COVID-19 patients was associated with negative attitudes.
Factors associated with knowledge, attitudes and preventive practices towards COVID-19 in health care professionals in Lima, Peru
Keywords: Health knowledge; Attitudes and practice; Health personnel; Coronavirus infections; Peru; https://purl.org/pe-repo/ocde/ford#3.03.08